2017
DOI: 10.1080/1028415x.2017.1415280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polydextrose and galactooligosaccharide increase exploratory behavior, improve recognition memory, and alter neurochemistry in the young pig

Abstract: These findings suggest that early life consumption of PDX/GOS supports recognition memory as measured by NOR while modulating the concentrations of VFAs in the colon, blood, and brain, as well as hippocampal serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 73 publications
3
48
1
Order By: Relevance
“…In contrast to our study, prebiotic supplementation had no effect on social interaction, however, the GOS: FOS receiving mice showed significantly increased number of prosocial events [2]. Other prebiotic mixtures also have behavioural modulatory capacities; juvenile rats and young pigs exposed to a prebiotic mixture of polydextrose and GOS showed reduced stress-induced behaviour and improved explorative behaviour, respectively [9,10]. These behavioural changes were accompanied with increased Lactobacillus spp.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In contrast to our study, prebiotic supplementation had no effect on social interaction, however, the GOS: FOS receiving mice showed significantly increased number of prosocial events [2]. Other prebiotic mixtures also have behavioural modulatory capacities; juvenile rats and young pigs exposed to a prebiotic mixture of polydextrose and GOS showed reduced stress-induced behaviour and improved explorative behaviour, respectively [9,10]. These behavioural changes were accompanied with increased Lactobacillus spp.…”
Section: Discussioncontrasting
confidence: 95%
“…As SCFAs are fermentation products from scGOS:lcFOS and SCFAs have been shown to reduce anxiety-like and depressive-like behaviour in mice [58], these mediators might play a role in the behavioural changes observed in our study. How this communication between the SCFAs and the brain occurs is unknown, however, signalling through the vagus nerve [10] or improved integrity of the blood brain barrier could play a role [59]. In the central nervous system, SCFAs (among others) play a role in the homeostasis of microglia cells, macrophage-like cells in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that components of human milk such as DHA [ 4 ], choline [ 5 ], and gangliosides [ 6 ] support brain development, and emerging research suggests milk oligosaccharides (ranging from 3–32 monosaccharide units in length [ 7 ]) may contribute to brain development as well [ 8 ]. Some milk oligosaccharides may act as prebiotics [ 8 ], and we recently demonstrated that pigs fed a combination of prebiotics demonstrated increased exploratory behavior and improved recognition memory [ 9 ]. Milk oligosaccharides are a heterogeneous group of oligosaccharides with diverse functions largely related to immunity and gut physiology [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison data are lacking in the pig model, but the use of maternal prebiotics can impact the progeny's growth, intestinal microbiota, morphology and immunity in pigs (Le Bourgot et al, 2014. The use of dietary prebiotics early in life in piglets also supported recognition memory and modulated the concentrations of SCFAs in the colon, blood and the brain, as well as hippocampal serotonin (Fleming et al, 2017). Interestingly, we recently showed that oral supplementation of butyrate might shape brain activity and plasticity .…”
Section: Impact Of Nutritional Preventive or Therapeutic Strategies Omentioning
confidence: 99%